A reassessment of explanations for discordant introgressions of mitochondrial and nuclear genomes. (16th August 2017) - Bonnet, Timothée; Leblois, Raphaël; Rousset, François; Crochet, Pierre‐André
Abstract: Hybridization is increasingly recognized as a significant evolutionary process, in particular because it can lead to introgression of genes from one species to another. A striking pattern of discordance in the amount of introgression between mitochondrial and nuclear markers exists such that substantial mitochondrial introgression is often found in combination with no or little nuclear introgression. Multiple mechanisms have been proposed to explain this discordance, including positive selection for introgressing mitochondrial variants, several types of sex‐biases, drift, negative selection against introgression in the nuclear genome, and spatial expansion. Most of these hypotheses are verbal, and have not been quantitatively evaluated so far. We use individual‐based, multilocus, computer simulations of secondary contact under a wide range of demographic and genetic scenarios to evaluate the ability of the different mechanisms to produce discordant introgression. Sex‐biases and spatial expansions fail to produce substantial mito‐nuclear discordance. Drift and nuclear selection can produce strong discordance, but only under a limited range of conditions. In contrast, selection on the mitochondrial genome produces strong discordance, particularly when dispersal rates are low. However, commonly used statistical tests have little power to detect this selection. Altogether, these results dismiss several popular hypotheses, and provide support for adaptive mitochondrial introgression.